149k views
5 votes
Answer: 14 (2+ 3 - 2 * 2) / (4² - 3²)

User Piotrekkr
by
7.1k points

2 Answers

4 votes
The answer is 14/7, which simplifies to 2.

Working:

2+3 = 5

2*2 = 4

5 - 4 = 1

4² = 16

3² = 9

16 - 9 = 7

(2 + 3 - 2 * 2) / (4² - 3²) = 1 / 7

Multiplying by 14, we get:

14 * (2 + 3 - 2 * 2) / (4² - 3²) = 14/7

Therefore, the final answer is 2
User Dzejkob
by
7.2k points
5 votes

Answer:

= 2

Explanation:

14(2+3-2*2) / (4²-3²)

= 14(2+3-4) / (16-9)

= 14(2-1) / 7

= 14(1) /7

= 14/7

= 2

User David Vicente
by
6.7k points